Die pädagogische Aufbereitung der Adjektivdeklination im Deutschen - Darski, Józef Paweł (Studia Germanica Posnaniensia, 2018)
The author analyses, in reference to his article of 1979, the manner of interpretation of the problem of adjective declension in German for glottodidactic purposes. He differentiates two types of declension of adjectives: non-determining and determining. On the basis of the principle of compensation with the endings of determinator he formulates an appropriate algorithm, which differentiates both kinds of declension.